Implementasi Nilai Kebangsaan sebagai Dasar Pendidikan Hukum untuk Anak Usia Dini - Subelo Wiyono; Saim Aksinudin; Yudi Prihartanto; Rusli Subrata (JECED : Journal of Early Childhood Education and Development, 2022)
The development of quality Indonesian human resources is strongly influenced by the success of early childhood education. Problems in the field of law today require solving strategies from various fields. Early childhood education is a very important field in participating in solving legal problems in Indonesia. This writing provides an overview of how early childhood education plays a role in building the world of law in the future. The writing method used is literature study supported by various kinds of discussions in the form of focus group discussions and national seminars. The philosophy of Pancasila which continues to be studied and practiced by teachers in the early childhood environment will foster awareness of a quality nation that can be proud of in the global arena. This is because education does not only develop the potential of senses and logic for all involved in it but also develops the potential of conscience, instinct, intuition and imagination.